Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T22:56:32+01:00
A) x=5+2y
5+2y+y=26
b) y=7-2x
5x-2*(7-2x)
c) 3x=8-4y
3*(9*8-9*4y)-7y=-14
d) 2y=7-5x
3x-8*(7-5x)=5
e)x=3-2y
5*3-5*2y-3y=2
f)y=2x+4
7x=5*2x+5*4
2010-01-08T22:56:48+01:00
A)x-2y=5
x+y=26
x= 5 + 2y
5 + 2y +y=26


b)2x+y=7
5x-2y=4
y=7 - 2x
5x-7 -2x =4


c)3x+4y=8
9x-7y=-14

3x= 8 - 4y/:3
9x-7y=-14

x = 8/3 - 4/3y
3*(8 - 4y)-7y=-14
d)
5x+2y=7
3x-6y=5

2y=7 - 5x
3x-12*(7-5x)=5

e)
2x=6-4y
5x-3y=2

x=3 - 2y
5*(3-2y)-3y=2
f)
3y=6x+12
7x=5y

y=2x + 4
7x=5 * (2x +4)
2010-01-08T23:38:49+01:00
A)x-2y=5
x+y=26
x=5+2y...
5+2y+y=26 →3y=26-5 → 3y=21 /:3 →y=7
x=5+2*7 → x=5+14 →x=19
spr.19-2*7 = 19-14=5
19+7=26

b)2x+y=7
5x-2y=4
y=7-2x...
5x-2(7-2x)=4 → 5x-14+4x = 4 → 9x=4+14 → 9x=18 /:9 → x=2
y=7-2x → y=7-2*2 → y=7-4 → y=3
spr.2*2 + 3 = 7
5*2 - 2*3 = 10 - 6 = 4

c)3x+4y=8
9x-7y=-14
3x=8-4y /:3 → x=8/3 - 4y/3....
ponieważ w mianowniku jest 3 a w drugim równaniu " 9x .." to można to skrócić i podzielić likwidując mianownik i pozostaje 3*...
3*(8 - 4y....)-7y=-14 →24-12y-7y=-14 → -19y = -14-24 → -19y=-38/(-19)→y=2
3x+4*2=8 → 3x=8-8 /3 → x=o
3*0+4*2=8
9*0-7*2=-14

d)
5x+2y=7
3x-6y=5
2y= 7-5x
3x-3*(7-5x)=5

e)2x=6-4y
5x-3y=2
x=3-2y
5*(3-2y)-3y=2

f)3y=6x+12
7x=5y
y=2x+4
7x=5*(2x+4)